Black nationalism in American politics and thought - Robinson, Dean E. (Cambridge University Press, 2001)
Black Nationalism in American Politics and Thought revisits the activism and arguments in support of separate black statehood from the mid-nineteenth century to the present, detailing the ways black nationalism historically mirrors broader currents in US politics and thought. This book challenges the idea that black nationalism is an essentially timeless, unchanging, and anti-assimilationist impulse with respect to the alternative goal of racial inclusion. It argues that black nationalism in the United States draws on analogous political strategy and thinking unique to specific historical eras – often inadvertently reproducing strategies and thinking responsible for racial inequality in the first place